2000
DOI: 10.1021/bi002189x
|View full text |Cite
|
Sign up to set email alerts
|

Clusterin Is an ATP−Independent Chaperone with Very Broad Substrate Specificity that Stabilizes Stressed Proteins in a Folding-Competent State

Abstract: We recently reported that the ubiquitous, secreted protein clusterin has chaperone activity in vitro [Humphreys et al. (1999) J. Biol. Chem. 274, 6875-6881]. In this study, we demonstrate that clusterin (i) inhibits stress-induced precipitation of a very broad range of structurally divergent protein substrates, (ii) binds irreversibly via an ATP-independent mechanism to stressed proteins to form solubilized high molecular weight complexes, (iii) lacks detectable ATPase activity, (iv) when acting alone, does no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
200
0
5

Year Published

2003
2003
2017
2017

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 232 publications
(214 citation statements)
references
References 29 publications
5
200
0
5
Order By: Relevance
“…Although identified two decades ago, its functions have not yet been fully elucidated (14,34). Previous reports have correlated clusterin expression with cell responses to stress (35), cell damage recovery (36,37), senescence (38,39), tumorigenesis (14,40), and apoptosis (14). In this report, we have demonstrated that clusterin expression is relatively uniform despite the regional differences of intestinal tumors in average size, frequency, and morphology (9,24).…”
Section: Discussionmentioning
confidence: 53%
“…Although identified two decades ago, its functions have not yet been fully elucidated (14,34). Previous reports have correlated clusterin expression with cell responses to stress (35), cell damage recovery (36,37), senescence (38,39), tumorigenesis (14,40), and apoptosis (14). In this report, we have demonstrated that clusterin expression is relatively uniform despite the regional differences of intestinal tumors in average size, frequency, and morphology (9,24).…”
Section: Discussionmentioning
confidence: 53%
“…These extracellular chaperones are also known to potently inhibit amorphous aggregation of proteins (10,11,35,38,39). We suggest that this small family of chaperones is likely to be an important part of a system that defends the human body against inappropriate extracellular protein aggregation, which can be either amorphous or amyloid in character.…”
Section: Discussionmentioning
confidence: 90%
“…Clusterin or apolipoprotein J is a molecular chaperone highly expressed in brain (Poon et al, 2000). Although, clusterin has been proposed as having a role in the regulation of apoptosis , in the neonatal brain clusterin accumulates in neurons dying with an excitotoxic phenotype following neonatal HI and appears to differentiate excitotoxic from caspase-dependent apoptosis (Han et al, 2001).…”
Section: Biochemical Evidence For Incomplete Execution Of Apoptotic Cmentioning
confidence: 99%